Using Graph Transformation Systems to Specify and Verify Data Abstractions - Baresi, Luciano; Ghezzi, Carlo; Mocci, Andrea; Monga, Mattia (Electronic Communications of the EASST, 2008)
This paper proposes an approach for the specification of the behavior of software components that implement data abstractions. By generalizing the approach of behavior models using graph transformation, we provide a concise specification for data abstractions that describes the relationship between the internal state, represented in a canonical form, and the observers of the component. Graph transformation also supports the generation of behavior models that are amenable to verification. To this end, we provide a translation approach into an LTL model on which we can express useful properties that can be model-checked with a SAT solver.